Acculturation and Postpartum Depressive Symptoms among Hispanic Women in the United States: Systematic Review. Issue 1 (January 2017) - Alhasanat, Dalia; Giurgescu, Carmen
Abstract: Purpose: The purpose of this review was to evaluate studies that examined the relationship between acculturation and postpartum depression (PPD) among immigrant and/or refugee women in the United States. Methods: A systematic, computer-assisted search of quantitative, English-language, peer-reviewed, published research articles was conducted in the Scopus, PsycINFO, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Maternity and Infant Care databases using the keyword terms of "postpartum depression" and "perinatal depression" in combination with "acculturation." Studies were included if they were conducted in the United States. Results: Seven studies met inclusion criteria. Three studies used longitudinal designs and four used cross-sectional designs. All were conducted with Hispanic women. Only one study used a diagnostic tool to measure PPD; the remaining studies used screening tools to measure postpartum depressive symptoms. Most studies used country of birth, country of residence, and language preferences to measure acculturation. Five studies reported acculturation was positively related to risk of postpartum depressive symptoms, and two studies reported no relationship. Clinical Implications: Higher levels of acculturation were related to higher risk of postpartum depressive symptoms in Hispanic women living in the United States. Nurses should have an understanding of stressors of immigrant women to guide their assessment and screening for postpartum depressive symptoms and make appropriate referrals. More research is needed to confirm the relationship between acculturation and PPD among immigrant women from different cultural backgrounds. Abstract : Higher levels of acculturation may be related to higher risk of postpartum depressive symptoms in Hispanic women living in the United States. Nurses should have an understanding of the stressors of immigrant women to guide their assessment and screening for postpartum depressive symptoms and make appropriate referrals.